Cardiovascular research in South Africa – Past, present, and future - Zühlke, LJ; Samodien, E (SA Heart Journal, 2026)
Cardiovascular diseases (CVD) remain one of the greatest global health challenges of our time. In the field of cardiology, South Africa (SA) produced several giants and champions whose contributions have been exceptional in their respective spheres. With the complexities required to reduce and prevent such illnesses, we draw inspiration and motivation from our history as we look to overcome future challenges. Here, we share some perspectives on future research priorities, including the usage of several facets of Artificial Intelligence (AI), such as AI-assisted echocardiography, which could unlock pathways to precision medicine, and adopting mobile health (mHealth) technology and wearable instruments for diagnostics, as well as clinical trials investigating the use of polypill interventions. This work echoes calls for health equity, recognising that the future strength of cardiovascular research will require initiatives that promote talent and provide opportunities to grow diverse capabilities within our country. Finally, we highlight the importance of community engagement and co-creation to foster trust and thereby enhance the uptake of interventions, including those aimed at promoting health literacy and education to support positive behaviour change in preventing CVDs and other non-communicable diseases (NCD).